2020
DOI: 10.3390/brainsci10050294
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Relationship between Sense of Agency and Post-Stroke Sensorimotor Deficits: A Longitudinal Case Study

Abstract: Post-stroke sensorimotor deficits impair voluntary movements. This impairment may alter a person’s sense of agency, which is the awareness of controlling one’s actions. A previous study showed that post-stroke patients incorrectly aligned themselves with others’ movements and proposed that their misattributions might be associated with their sensorimotor deficits. To investigate this hypothesis, the present study compared the agency dynamics in a post-stroke patient A (PA) with sensorimotor deficits, who rarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…The second is that it is unclear how SoA interacts with motor performance and changes over time. We have reported in a case series that SoA is related to the recovery processes of motor paralysis after a stroke [ 33 ]. Thus, it is necessary to discuss the relationship between SoA and the processes of functional recovery after a brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…The second is that it is unclear how SoA interacts with motor performance and changes over time. We have reported in a case series that SoA is related to the recovery processes of motor paralysis after a stroke [ 33 ]. Thus, it is necessary to discuss the relationship between SoA and the processes of functional recovery after a brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sense of agency can be grounded within the sensorimotor system in motor control [ 3 ], post-stroke sensorimotor deficits may result in altered self-other attribution (i.e., misattribution) through disturbing the sensorimotor system. Our previous studies examined this possibility [ 13 , 14 ]. The results showed that patients with post-stroke sensorimotor deficits compared with healthy elderly participants, significantly misattributed the cursor movements that were provided to participants as visual feedback of their movements [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that patients with post-stroke sensorimotor deficits compared with healthy elderly participants, significantly misattributed the cursor movements that were provided to participants as visual feedback of their movements [ 13 ]. Furthermore, a longitudinal case study indicated that such misattributions may depend on the sensorimotor deficit severity and paretic upper limb activity [ 14 ]. These studies suggested that sensorimotor deficits are involved in making misattributions; however, it remains unclear why such patients made the misattributions and how they made self-other attributions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multisensory training may be beneficial in preventing maladaptive brain reorganization and may yield useful information, leading to appropriate clinical treatment when altered sensory information is present. These findings could be relevant in cases in which the sense of agency changes according to the sensorimotor deficit severity and paretic upper limb activity [ 34 ] or, for example, in apraxia [ 35 ]. These stimulating results enhance our knowledge and interest for further basic and clinical investigations on the role of body and action in clinical and rehabilitation [ 26 , 36 , 37 , 38 ].…”
mentioning
confidence: 99%